Implementation of Reforms in the Field of Preschool Education in Surkhondarya Region (On the Example Of 2017-2021) - Abdugani Kilichovich Tukhtaev (Peerian Journals Publishing, 2022)
A number of positive steps have been taken in Termez district to ensure the implementation of the decree of the President "On measures to further improve the system of preschool education in 2017-2021." In 2018, the number of boys and girls involved in preschool education in the territory of Termez district amounted to 10,325 people. In July 2019, two preschools (MTCs) were commissioned in Shargun and Sangardak mahallas on a state and partnership basis. By the end of 2021, the number of preschool organizations in the region reached 2,044, including 382 public preschools, 148 private preschools, and 1,506 family nongovernmental preschools. Coverage increased from 41.5% at the beginning of the year to 57%.
Keywords: Termez district; Shargun city; Boysun; Healthy generation program